Lower cardiac index levels relate to lower cerebral blood flow in older adults. (5th December 2017) - Jefferson, Angela L.; Liu, Dandan; Gupta, Deepak K.; Pechman, Kimberly R.; Watchmaker, Jennifer M.; Gordon, Elizabeth A.; Rane, Swati; Bell, Susan P.; Mendes, Lisa A.; Davis, L. Taylor; Gifford, Katherine A.; Hohman, Timothy J.; et al.
Abstract : Objective: To assess cross-sectionally whether lower cardiac index relates to lower resting cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) among older adults. Methods: Vanderbilt Memory & Aging Project participants free of stroke, dementia, and heart failure were studied (n = 314, age 73 ± 7 years, 59% male, 39% with mild cognitive impairment). Cardiac index (liters per minute per meter squared) was quantified from echocardiography. Resting CBF (milliliters per 100 grams per minute) and hypercapnia-induced CVR were quantified from pseudo-continuous arterial spin-labeling MRI. Linear regressions with ordinary least-square estimates related cardiac index to regional CBF, with adjustment for age, education, race/ethnicity, Framingham Stroke Risk Profile score (systolic blood pressure, antihypertensive medication use, diabetes mellitus, current cigarette smoking, left ventricular hypertrophy, prevalent cardiovascular disease [CVD], atrial fibrillation), APOE ε4 status, cognitive diagnosis, and regional tissue volume. Results: Lower cardiac index corresponded to lower resting CBF in the left (β = 2.4, p = 0.001) and right (β = 2.5, p = 0.001) temporal lobes. Results were similar when participants with prevalent CVD and atrial fibrillation were excluded (left temporal lobe β = 2.3, p = 0.003; right temporal lobe β = 2.5, p = 0.003). Cardiac index was unrelated to CBF in other regions assessed ( p > 0.25) and CVR in all regions ( p > 0.05). In secondary cardiac index × cognitive diagnosis interaction models, cardiac index and CBF associations were present only in cognitively normal participants and affected a majority of regions assessed with effects strongest in the left ( p < 0.0001) and right ( p < 0.0001) temporal lobes. Conclusions: Among older adults without stroke, dementia, or heart failure, systemic blood flow correlates with cerebral CBF in the temporal lobe, independently of prevalent CVD, but not CVR.